2019
DOI: 10.1063/1674-0068/cjcp1901007
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals interactions in bimolecular reactions

Abstract: The van der Waals (vdW) interaction is very important in fields of physics, biology and chemistry, and its role in reaction dynamics is an issue of great interest. In this review, we focus on the recent progresses in the theoretical and experimental studies on the vdW interaction in bimolecular reactions. In particular, we review those studies that have advanced our understanding of how the vdW interaction can strongly influence the dynamics in both direct activated and complex-forming reactions, and further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…Comparing to the atom-atom interaction, on the other hand, the dipole-dipole interaction is a long-range van der Waals interaction. Previous studies have shown that van der Waals interactions play important roles in molecular reaction dynamics (Skouteris et al, 1999;Shen et al, 2017;Cao et al, 2019;Wu et al, 2019). Hence, the long-range dipole-dipole interaction might lead to discoveries of new quantum effects, based on which novel technologies could be developed (Chen and Yan, 2019).…”
Section: Spectroscopic Constantsmentioning
confidence: 99%
“…Comparing to the atom-atom interaction, on the other hand, the dipole-dipole interaction is a long-range van der Waals interaction. Previous studies have shown that van der Waals interactions play important roles in molecular reaction dynamics (Skouteris et al, 1999;Shen et al, 2017;Cao et al, 2019;Wu et al, 2019). Hence, the long-range dipole-dipole interaction might lead to discoveries of new quantum effects, based on which novel technologies could be developed (Chen and Yan, 2019).…”
Section: Spectroscopic Constantsmentioning
confidence: 99%
“…So far only a few molecules including SrF, CaF, and YO have been cooled to the ultracold temperature experimentally, and there is an urgent need to search for more suitable molecular candidates for laser cooling. Recently, a number of theoretical efforts have been made in searching for promising molecular laser cooling candidates (Wells and Lane, 2011a;Fu et al, 2016a;Cao et al, 2019;González-Sánchez et al, 2019;Xu et al, 2019). It is generally accepted (Di Rosa, 2004;Fu et al, 2016b) that, a suitable laser-cooling candidate must meet the following three criteria: highly diagonal Franck-Condon factors (FCFs), a short lifetime, and no intermediate electronic-state interference.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now only a very limited number of molecules have been successfully cooled to the ultracold temperatures experimentally. So there is an urgent necessity to search for more promising laser cooling candidates, and some theoretical efforts have been made to identify more candidates for laser cooling ( Wells and Lane, 2011 ; Fu et al, 2017 ; Cao et al, 2019 ; Moussa et al, 2021 ). It is known ( Fu et al, 2016 ; Yuan et al, 2019 ; Li et al, 2021 ) that, a suitable candidate for laser cooling needs to satisfy three criteria: highly diagonal Franck-Condon factors (FCFs), an extremely short radiative lifetime, and no interference from the intermediate electronic states.…”
Section: Introductionmentioning
confidence: 99%